Hyperparathyroidism secondary to parathyroid carcinoma - Cruz Jesus, Lourdes (1998)
The authors describe a case of parathyroid carcinoma in a 40 year old patient, who presented with clinical symptoms of six month duration, characterized by generalized bone pain, muscle weakness, polydipsia, polyuria, marked lassitude, and a palpable cervical nodule. Laboratorial results revealed severe hypercalcaemia, raised alkaline phosphatase, renal failure and extremely high levels of intact parathyroid hormone (PTHi). Radiological imaging revealed the exis tence of cystic fibrosing osteitis and parentchimal calcification of renal tissue. Studies of the neck showed a heterogenous structure of the left lobe of the thyroid. Following surgical excision of the tumour complete remission of clinical symptoms, as well as normalization of laboratory, values, were observed. Nevertheless, ten months after surgery a new rise in PTHi level, consequent hypercalcaemia, and cervical adenopathy ocurred, requiring surgical removal once again. The authors present the clinical case as well as therapeutic strategies.